1984
DOI: 10.1055/s-0038-1661057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Yoga on Blood Coagulation

Abstract: SummaryYoga is known to induce beneficial effects on physiological, biochemical and mental functions in man. Its effects on blood coagulation are not known. A study was conducted in seven previously untrained male adults who underwent a combination of yogic exercises, daily for one hour, over a period of four months. Parameters of blood coagulation were estimated before and after the end of yoga training. The following changes were observed: Fibrinolytic activity increased significantly with a concomitant fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Furthermore, there was preliminary evidence that regular yoga exercise training reduces oxidative stress markers and fibrinogen levels in non-randomized, controlled, and uncontrolled trials. [37] In our study the decreased concentration of MDA (although not statistically significant) after four months, in ESRD patients in the Hatha yoga exercise group, indicated that there was a reduction in lipoperoxidation.…”
Section: Discussionmentioning
confidence: 41%
“…Furthermore, there was preliminary evidence that regular yoga exercise training reduces oxidative stress markers and fibrinogen levels in non-randomized, controlled, and uncontrolled trials. [37] In our study the decreased concentration of MDA (although not statistically significant) after four months, in ESRD patients in the Hatha yoga exercise group, indicated that there was a reduction in lipoperoxidation.…”
Section: Discussionmentioning
confidence: 41%
“…Chohan et al . [20] looked at blood coagulation in normal adults, who underwent a combination of yogic exercises for one hour daily for four months, and noted that yoga induced a state of blood hypocoagulability. The changes that occur during pregnancy create a hypercoagulable milieu, which is thought to be protective especially at the time of labor, for preventing excessive hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocyte aggregation and deformability and fibrinogen levels are also determinants of WBV that could explain the lower WBV among yoga practitioners. Yoga has been demonstrated to reduce fibrinogen levels which could facilitate improvements in WBV through reductions in erythrocyte aggregation ( 6 ). Erythrocyte adhesiveness and aggregation are indicative of inflammation ( 2 ) and oxidative stress ( 14 ), both of which have been significantly altered with the practice of Hatha yoga and yogic techniques in healthy adults ( 18 , 25 ) and in patients with heart failure ( 22 ) and diabetes ( 12 , 26 ).…”
Section: Discussionmentioning
confidence: 99%